PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KOMPETENSI KOGNITIF SISWA DI SDIT JAMIYYATUL MUSTAQIM - Diona Aulia Mahardika; Iskandar Yusuf (STKIP Subang, 2026)
ABSTRACT This study aimed to determine the effect of Islamic Religious Education (PAI) teachers' pedagogical competence on the cognitive competence of fifth-grade students at SDIT Jamiyyatul Mustaqim. The study was motivated by the fact that students' cognitive competence is influenced not only by their own abilities but also by the quality of teachers' pedagogical competence in managing the learning process. This research employed a quantitative approach with a correlational design. The population consisted of all fifth-grade students at SDIT Jamiyyatul Mustaqim, totaling 20 students, who were selected using total sampling. Data were collected through questionnaires measuring teachers' pedagogical competence and students' cognitive competence. The instruments were tested for validity and reliability, and the data were analyzed using descriptive statistics, prerequisite tests, simple linear regression, the t-test, and the coefficient of determination with IBM SPSS. The findings revealed a positive relationship between teachers' pedagogical competence and students' cognitive competence, with a correlation coefficient (R) of 0.355. However, the effect was not statistically significant, as indicated by a significance value of 0.125 (>0.05) and tcount (1.609) < ttable (2.101). The coefficient of determination (R²) of 0.126 indicated that teachers' pedagogical competence contributed 12.6% to students' cognitive competence, while the remaining 87.4% was influenced by other factors. Therefore, teachers' pedagogical competence was not found to have a significant effect on students' cognitive competence.